DRONKENSKAP IN DIE SUID -AFRIKAANSE WEERMAG NA AANLIEDING VAN ARTIKEL 33A VAN DIE REGLEMENT VAN DISSIPLINE - Van Tromp, J (Scientia Militaria - South African Journal of Military Studies, 2012)
The SADF member has. apart from the civilian laws. also a military discipline code imposed on him. This code differs from the ordinary laws and in this article special attention is paid to the soldier and drunkenness. Interesting aspects such as the fact that a soldier can be convicted on evidence given by laymen are discussed. The fact that a member of the SADF is considered to be on duty 24 hours a day implies that to be drunk in his private home after hours also makes him guilty in terms of article 33aof the Military Discipline Code.